Blockchain applications and sustainability issues - Roberto Leonardo Rana; Pasquale Giungato; Angela Tarabella; Caterina Tricase (Amfiteatru Economic Journal, 2019)
Blockchain, a distributed and democratically-sustained public register of the transactions of the digital currency "Bitcoin", proposed by Satoshi Nakamoto a pseudonym of a hided developer in 2009, has been the driver of a huge number of initiatives devoted to develop and implement a peer-to-peer distributed database, and with no central authority created as an open source software. Expansion of Bitcoin, as well as other digital currencies, has been due to lower transaction costs, high security protocols and lack of inflation with respect to fiat money and no need of a clearing entity or a central bank. Although, environmental issues related to the use of this currency and, in particular, in the energy consumes, have been raised by the scientific community, but no signals of limiting factors have been detected until now. The hidden in the wings blockchain technology has been recognized the driver of innovation in various fields, contributing to create a more sustainable world. The purpose of this paper is to describe both the recent trends in the applications of the blockchain technology in the cryptocurrencies market and the new projects considering the environmental sustainability (energy consumption, materials depletion) and social impacts. The contribute of blockchain in reducing and accelerating bureaucracy and incentivizing environmentally friendly behaviour, has been discussed. Although the environmental issues related to the energy consumed in Bitcoin mining may scare companies in adopting the new technology, there is no evidence of limiting factors or carrying capacity of the entire system. In future the development of a less energy intensive alternative for validating the blocks to stack in the distributed database, would render the blockchain the ideal candidate for the applicability of sustainability paradigms in the economic, environmental and social sectors.
Keywords: O33; 330; blockchain; bitcoin; sustainability; energy consumption; cryptocurrency